A Transitional Model for the Evaluation of West Nile Virus Transmission in Italy. Issue 5 (10th November 2014) - Calistri, P.; Savini, L.; Candeloro, L.; Di Sabatino, D.; Cito, F.; Bruno, R.; Danzetta, M. L.
Summary: In August 2008, after 10 years of apparent silence, West Nile virus (WNV) infection re‐emerged in northern Italy, spreading through the territories of three regions. In the following years, new cases occurred in the same area and additional foci of infection were observed in central and southern Italy, involving also Sicily and Sardinia islands. The Italian Ministry of Health ordered to test by RT‐PCR all blood and organ donors from 15th June to 15th November of each year in the infected areas. The period at risk of WNV transmission was defined on the basis of literature data, but a more scientific estimation of the transmission season, under Italian circumstances, needs to be performed. A transitional model previously developed by other Authors was applied and adapted to Italian circumstances, to describe and quantify the WNV transmission cycle between birds and mosquitoes. Culex spp. was considered the main vector, and mosquito parameters were adapted to this genus. Magpies ( Pica pica ) were considered the main bird host. The model was partially validated through the results of the entomological surveys carried out in central Italy and in Po Valley. The results of the transitional model permitted to calculate the basic reproduction number ( R 0 ) during 2010 for the whole Italian territory at 1 km of spatial resolution, estimating the risk of WNV transmission during the year and creating detailed risk maps for Italy. The mean values of R 0 for the whole Italy varied between 0.4 and 4.8, with values >1 from the end of May to the middle of September. The coastal and flat zones of Italy showed the highest R 0 values. Although partially validated, the model showed a substantial acceptable capacity of defining the period at major risk of WNV transmission in Italy, helping Public health authorities in the application of appropriate and timely control and preventive measures.